A Second Shot, A True Crime Episode - Dasgupta, Sunil; Weissberg, Michael (I Hate Politics Podcast, 2025)
On October 23, 1971, Deputy Sheriff James T. Hall was killed in the parking lot of Manor Country Club, the center of a wealthy golf course community between the city of Rockville and Olney, MD. The case remained unsolved for 50 years, until 2021, when cold case detectives finally took another look at the urging of Hall's daughter, Carolyn Philo, who had long moved to Dallas, Texas, where she told the story of her father’s murder to her doctor, Michael Weissberg, a moonlighting crime writer. As cold case detectives pursued neglected leads, Weissberg began writing the book. Weissberg joined Sunil Dasgupta to talk about the recently-published book, A Second Shot: https://a.co/d/9rHb3cp. Music by Silver Spring power pop band, The Airport77s.
Keywords: I Hate Politics